Miniaturized capillary ion chromatograph with UV light‐emitting diode based indirect absorbance detection for anion analysis in potable and environmental waters. Issue 16 (22nd August 2018) - Murray, Eoin; Li, Yan; Currivan, Sinead A.; Moore, Breda; Morrin, Aoife; Diamond, Dermot; Macka, Mirek; Paull, Brett
Abstract: A miniaturized, flexible, and low‐cost capillary ion chromatography system has been developed for anion analysis in water. The ion chromatography has an open platform, modular design, and allows for ease of modification. The assembled platform weighs ca. 0.6 kg and is 25 × 25 cm in size. Isocratic separation of common anions (F –, Cl –, NO2 –, Br –, and NO3 – ) could be achieved in under 15 min using sodium benzoate eluent at a flow rate of 3 μL/min, a packed capillary column (0.150 × 150 mm) containing Waters IC‐Pak 10 μm anion exchange resin, and light‐emitting diode based indirect UV detection. Several low UV light‐emitting diodes were assessed in terms of sensitivity, including a new 235 nm light‐emitting diode, however, the highest sensitivity was demonstrated using a 255 nm light‐emitting diode. Linear calibration ranges applicable to typical natural water analysis were obtained. For retention time and peak area repeatability, relative standard deviation values ranged from 0.60–0.95 and 1.95–3.53%, respectively. Several water samples were analysed and accuracy (recovery) was demonstrated through analysis of a prepared mixed anion standard. Relative errors of –0.36, –1.25, –0.80, and –0.76% were obtained for fluoride, chloride, nitrite, and nitrate, respectively.